Thermally stable single atom Pt/m-Al2O3 for selective hydrogenation and CO oxidation - Zailei Zhang (Nature Portfolio, 2017)
Using precious noble elements as single atom metal catalysts is highly desirable and effective. Here the authors show the use of platinum atom catalysts anchored in mesoporous Al2O3for selective hydrogenation and CO oxidation that have better stability and performance compared to their nanoparticle counterparts.